TEACHING-LEARNING IN MONITORING OF GROWTH AND DEVELOPMENT OF THE CHILD (Fiep Bulletin - online, 2013)
This study focuses on the approach to the teaching-learning process in relation to the monitoring of growth and development of the child, to examine the perceptions of students in the course of undergraduate nursing education in order that process, through a methodology descriptive and exploratory, to seal qualitative, to sum up, through this study that there is a need to focus strongly the paradigm of Health Promotion, partially seized by students along the teaching-learning process, because they tend to act in accordance with the model of health care imprint of biological, curative and medical.
Keywords: Students; Health Occupations; Infant Care; Health Care (Public Health).